Re-Infection of COVID-19 at Dr. Moewardi General Hospital, Surakarta, from March 2020 to June 2021 - Jatu Aphridasari (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: COVID-19 reinfection has been identified and is being studied. Several risk factors, including being a health worker and having A blood type, are linked to reinfection, and comorbidities such as hypertension, obesity, diabetes, and asthma influence the disease's severity. To identify mutational variations associated with viral virulence and spread, genetic studies are required. The purpose of this study is to determine the prevalence of SARS-CoV-2 reinfection, as well as patient characteristics and risk factors related to SARS-CoV-2 reinfection. Subjects and Method: This is a retrospective cohort study using data from the medical records of patients with COVID-19 reinfection treated at the Dr. Moewardi General Hospital (RSDM) Surakarta from March 2020 to June 2021. A sample was collected from 19 men and 20 women. The degree of COVID-19 infection is the dependent variable. Gender, occupation, comorbidities, and immunization history were the independent variables. The entire sampling method was employed in this investiga¬tion (consecutive sampling). Data is handled in Microsoft Excel 2010, and statistical analysis is performed in SPSS version 20.0. Results: COVID-19 re-infection is equally likely in men and women. The average patient age was 42 years, with patients ranging in age from 25 to 73 years. Patients in the study were classified as either health workers or non-health workers, with 29 (76.3%) and 9 (23.7%) respectively. Due of restricted resources, the average period of COVID-19 re-infection is 197.6 +/- 97 days without genomic sequence investigation. Comorbidities were discovered in 11 of 38 COVID-19 reinfection patients (29%) Only 6 individuals (15.8%) with COVID-19 reinfection had a history of vaccination. Conclusion: Using convalescent plasma to treat patients with COVID-19 is a rather safe practice. Our analysis demonstrated that the administration of convalescent plasma did not enhance survival or clinical outcomes for COVID-19 patients with moderate to severe disease. Keywords: COVID-19, COVID-19 reinfection, health workers, comorbidity Correspondence: Jatu Aphridasari. Department of Pulmonology and Respiratory Medicine, Dr. Moewardi General Hospital, Surakarta – Indonesia. jatuparu@staff.uns.ac.id. Mobile: +6281289991329.